2019
DOI: 10.1038/s41598-019-49582-3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during preoperative therapy increases tumor vascularity in pancreatic tumor patients

Abstract: The efficacy of chemotherapy is reduced by dysfunctional tumor vasculature, which may limit chemotherapy delivery to tumors. Preclinical studies have shown that moderate aerobic exercise improves tumor vascular function and increases chemotherapy efficacy in mouse models, but the effect of exercise on human tumor vasculature has not yet been determined. Here, we demonstrate that exercise remodels the tumor vasculature, accelerates the regression, and delays the regrowth of pancreatic ductal adenocarcinoma in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 9 publications
2
50
0
2
Order By: Relevance
“…In one detailed study on a mouse xenograft model of PDAC, the combination of gemcitabine plus treadmill walking inhibited tumor growth significantly more than gemcitabine alone [336]. The same effect was seen in a PDX model of PDAC (Figure 18A) [38]. The latter study also showed that the time taken for tumors to regress was significantly (ca.…”
Section: Exercisementioning
confidence: 73%
See 3 more Smart Citations
“…In one detailed study on a mouse xenograft model of PDAC, the combination of gemcitabine plus treadmill walking inhibited tumor growth significantly more than gemcitabine alone [336]. The same effect was seen in a PDX model of PDAC (Figure 18A) [38]. The latter study also showed that the time taken for tumors to regress was significantly (ca.…”
Section: Exercisementioning
confidence: 73%
“…Therefore, one possible method for improving outcomes for patients receiving standard chemotherapy is to improve the vasculature within the tumor. In addition, exercise can reduce fatigue, fitness loss, as well as improve mental health and the psychosocial downside of treatment [38].…”
Section: Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in children and AYA with cancer, malnutrition—including both over and undernutrition—is a risk factor for inferior cancer-related outcomes [ 4 ] and PA is associated with improved quality of life and physical function [ 5 ]. There are also emerging preclinical data that suggest that PA may improve tumor response to treatment [ 6 , 7 ] and that obesity may reduce tumor response to treatment via adipocyte signaling [ 8 ]. Both the intake and expenditure aspects of the EB equation as they relate to cancer outcomes will be reviewed briefly below.…”
Section: Introductionmentioning
confidence: 99%